2021
DOI: 10.1007/s13201-021-01517-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on operating parameters and cost using an electrocoagulation process for wastewater treatment

Abstract: Wastewater generated from different sources affects the health of living organisms and the natural environment due to the availability of different pollutants. Electrocoagulation (EC) is a good technology implemented for wastewater treatment before discharging to an environment as effluents. The electrocoagulation process is an effective method to the remove the color, chemical oxygen demand (COD), turbidity, and consumption of less energy from wastewater by considering different operating parameters. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The good removal of contaminants from the water was achieved while the electric current was a progressive increase [ 22 ]. This can be observed that the rate of coagulant and bubble generation is determined by the applied current, and this can improve the effectiveness of pollutant removal [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The good removal of contaminants from the water was achieved while the electric current was a progressive increase [ 22 ]. This can be observed that the rate of coagulant and bubble generation is determined by the applied current, and this can improve the effectiveness of pollutant removal [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…e removal efficiencies of color [22], phosphate [42], TDS [43], COD [36,44], and BOD [44] were calculated using equations ((1)-( 5)).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations